Non-Formal Education Activities in a Town Park: The Case of Kuršėnai Park - Poškienė, Rasa; Gaučaitė, Ramutė (Jaunųjų mokslininkų darbai, 2015)
The paper analyzes non-formal education activities provided in a town park of Kuršėnai, visitors’ needs for non-formal education activities and opinion about them. Understanding that a town park can be used for educational and recreational purposes and self-expression it is important to know park visitors’ and local community opinion about the availability and attractiveness of activities there. Insights into the issue will allow to develop and offer such activities. A town park mainly provides an opportunity for local community to satisfy its needs for recreation meanwhile little attention is paid to non-formal education and thus the potential of such open spaces remains untapped therefore it is important to analyze the experience of Kuršėnai park, provided non-formal education activities, the need of the local community for them and opinion. Such sociocultural activities that address individual and community needs should be offered in a town park and its biological, social, cultural infrastructure should be used.